THE INFLUENCE OF PRICE, ADVERTISING ATTRACTIVENESS, BRAND AND PRODUCT QUALITY ON DECISIONS TO PURCHASE USED CLOTHING - Wulandari, Ani (Sekolah tinggi ilmu ekonomi pemuda, 2024)
The used clothing is currently a fashion trend, especially among teenagers. The popularity of second-hand clothing is increasing because most people consider second-hand clothing as unique and classic fashion. Thus increasing people's buying interest in used clothing products. Buying interest itself is consumer behavior that occurs as a reaction to an object which indicates a person's desire to buy an item. The aim of this research is to determine the influence of price (X1), advertising attractiveness (X2), brand (X3) and product quality (X4) on purchasing decisions (Y) for used clothes at the Rafa thrift store in Surabaya. The approach to this research uses a quantitative approach, with questionnaire data collection techniques. The population in this study consisted of 105 Thrift Rafa Store used clothing customers in June-August 2024. The sample was determined using the formula proposed by Slovin to obtain a sample size of 51. Data obtained from distributing questionnaires will be processed using the SPSS program. The results of the data obtained from the T test is that all independent variables have a positive significant influence partially towards purchase decision. As for simultaneous influence, all independent variables all together has a positive significant influence towards purchasing decisions, with the variable of brand having the most dominant influence on purchasing decisions. Keywords: Price, Advertising Attractiveness, Brand, Product Quality, Purchasing Decisions, Used clothing